2019
DOI: 10.1016/j.jtrangeo.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cycling patterns and attitudes towards cycling in a sample of European regular cyclists

Abstract: Men cycle more than women and gender differences in perceptions and attitudes towards cycling may be influenced by such difference in bicycle use. However, to our knowledge, no previous research has focused on gender differences among regular cyclists. In our study, we investigated gender differences in attitudes towards cycling and towards cycling infrastructure, purpose of cycling, risk perception, and exposure to severe crashes in a large sample of regular cyclists. Following a cross-sectional design, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 50 publications
4
24
0
1
Order By: Relevance
“…The gender gap in cycling is due to a differentiated response to the attractiveness of cycling, as women require a more conducive environment. This suggests a need to improve the cycling environment to attract more female cyclists [31] by including them in the design of cycling infrastructure [32]. In general, women undertake household tasks, carry more bags than men, and travel more often with children; therefore, their participation in the design of bicycles is important.…”
Section: Women's Mobility and Travel Behaviourmentioning
confidence: 99%
“…The gender gap in cycling is due to a differentiated response to the attractiveness of cycling, as women require a more conducive environment. This suggests a need to improve the cycling environment to attract more female cyclists [31] by including them in the design of cycling infrastructure [32]. In general, women undertake household tasks, carry more bags than men, and travel more often with children; therefore, their participation in the design of bicycles is important.…”
Section: Women's Mobility and Travel Behaviourmentioning
confidence: 99%
“…We used data on cyclists' crashes in Italy, which can be considered a country with low-cycling culture or emerging cycling culture (Aldred & Jungnickel, 2014;Oosterhuis, 2016). Compared to cyclists in other European countries, Italian cyclists tend to report positive attitudes towards cyclists but also the lowest ratings on infrastructure quality and provisions (Prati et al, 2019). According to the Special Eurobarometer 422a -Quality of transport (European Commission, 2014), bicycle is the most used mode of transport in Italy for 8% of women and for 4% of men.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that bicycle use tends to be predominant among men. Prati et al [ 51 ] conducted a survey with regular cyclists in six European countries, and gender differences in attitudes towards cycling tended to disappear. Indeed, within short and medium distances, cycling habits could be crucial to reducing car use.…”
Section: Discussionmentioning
confidence: 99%